Zona Khusus Kepemilikan Asing dan Restrukturisasi Kebijakan Pertanahan untuk Pertumbuhan Investasi dan Family Office di Indonesia: Tinjauan Integratif dan Analisis Isi - I Made Herman Susanto; Dani Lukmito Utomo; Wehelmina Linda Herlophina Dethan; Ni Luh Putu Ari Saptarini Widiastuti; Ni Ketut Sriati (Tunas Agraria, 2026)
The global investment wave from Ultra-High-Net-Worth Individuals (UHNWIs) and Family Offices (FOs) faces a paradox in Indonesia: policy pressures to attract long-term investment clash with foreign land ownership regulations that are considered rigid and vulnerable to illegal practices such as nominees. This qualitative research, using an integrative literature review and content analysis approach to existing regulations and literature documents, aims to (1) synthesize literature findings on FOs and foreign land ownership policies, (2) evaluate the opportunities for establishing 'Special Zones' as an adaptive policy solution, and (3) formulate priority strategies for the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN). The research results identify a fundamental tension between investment attractiveness and sustainability imperatives. As a solution, this study recommends policy restructuring that focuses on the creation of Special Zones for Foreign Ownership (ZKKA) based on the Digital RDTR, the development of a risk-based ownership verification system, reform of land services digitalization policies, specific regulations for investment and FOs, and human resource capacity building. This multidimensional strategy is expected to transform challenges into opportunities to attract strategic investment while ensuring agrarian sovereignty, environmental sustainability, and social justice.   Gelombang investasi global dari Ultra-High-Net-Worth Individuals (UHNWIs) dan Family Office (FO) menghadapi paradoks di Indonesia: desakan kebijakan untuk menarik investasi jangka panjang berbenturan dengan regulasi kepemilikan asing atas tanah yang dianggap kaku dan rentan terhadap praktik ilegal seperti nominee. Penelitian kualitatif dengan pendekatan Integrative Literature Review dan Content Analysis terhadap regulasi eksisting dan dokumen literatur ini bertujuan untuk: (1) mensintesis temuan literatur mengenai FO dan kebijakan kepemilikan asing atas tanah, (2) mengevaluasi peluang pembentukan 'Zona Khusus' sebagai solusi kebijakan adaptif, serta (3) merumuskan strategi prioritas bagi Kementerian Agraria dan Tata Ruang/Badan Pertanahan Nasional (ATR/BPN). Hasil penelitian mengidentifikasi ketegangan mendasar antara daya tarik investasi dan imperatif keberlanjutan. Sebagai solusi, penelitian ini merekomendasikan restrukturisasi kebijakan yang berfokus pada penciptaan Zona Khusus Kepemilikan Asing (ZKKA) berbasis RDTR Digital, pengembangan sistem verifikasi kepemilikan berbasis risiko, reformasi kebijakan digitalisasi layanan pertanahan, regulasi khusus untuk investasi dan FO, dan peningkatan kapasitas SDM. Strategi multidimensi ini diharapkan dapat mengubah tantangan menjadi peluang untuk menarik investasi strategis sekaligus menjamin kedaulatan agraria, keberlanjutan lingkungan, dan keadilan sosial.